The Constitutional Bases for Securing the Independence of the Judiciary - Ghazinyan , G. (Bulletin of Yerevan University C: Jurisprudence, 2017)
The article is focused on the constitutional guarantees of the independence of judicial power in the context of the constitutional amendments of 6 December 2015. The article presents the regulations related to the status, composition and formation of the Council of Justice and its successor High Council for Judcicary as constitutional bodies responsible for guaranteeing the independence of the judiciary based on the analyzis of the existing legislative regulations, issues rising in practice and the new constitutional amendments aimed to solve them. The article also outlines the advantages and disadvantages of the current and new constitutional regulations in regard the appointment of judges
Keywords: independence of judicial power, Council of Justice, High Council for Judiciary, judge memebers, non-judge members, National Assembly of the RA, President of the RA